Relationship Between the Institutional Environment and Country Risk - Arellano, Melissa (2024)
The analysis of Country Risk and its determinants has gained significant importance in economic theory. In this context, the influence of the institutional environment on Country Risk has been extensively investigated and documented, as factors such as regulations, the justice system, and the quality of governance play crucial roles in economic stability. This study examines the relationship between the institutional environment and Country Risk in seventeen countries across Latin America, the Caribbean, Asia, and Europe. The main hypothesis of this work posits that a deterioration in institutional quality in developing countries is linked to an increase in the level of Country Risk. To demonstrate this hypothesis, a Feasible Generalized Least Squares (FGLS) model is estimated using panel data from 2002 to 2019. The results support the stated hypothesis, with the variables right of expression and efficiency of law standing out as the main factors contributing to the reduction of Country Risk.